2021
DOI: 10.1097/fjc.0000000000000977
|View full text |Cite
|
Sign up to set email alerts
|

Perindopril Reduces Arterial Pressure and Does Not Inhibit Exercise-Induced Angiogenesis in Spontaneously Hypertensive Rats

Abstract: Sympathetic activity, arteriolar structure, and angiogenesis are important mechanisms modulating hypertension and this study aimed to analyze the effects of perindopril treatment, associated or not with exercise training, on the mechanisms that control blood pressure (BP) in hypertensive rats. Spontaneously hypertensive rats (SHR) were allocated into 4 groups: 1/sedentary (S); 2/perindopril (P, 3.0 mg/kg/d); 3/trained (T); and 4/trained + perindopril (TP). Wistar rats were used as normotensive sedentary contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 77 publications
3
16
0
Order By: Relevance
“…All animals were adapted for 5 days to the cylindrical acrylic tube that kept the rats at rest and, during the 8-weeks period of combined training, systolic blood pressure assessments were performed at the beginning, after 30 and 60 days, as stated in Figure 1 , following the procedures already published ( Miotto et al, 2021a ; Miotto et al, 2021b ). A cuff was positioned around the tail of the animals and systolic blood pressure (SBP) was recorded by tail-cuff plethysmography system (PanLab LE5001, Barcelona, Spain).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All animals were adapted for 5 days to the cylindrical acrylic tube that kept the rats at rest and, during the 8-weeks period of combined training, systolic blood pressure assessments were performed at the beginning, after 30 and 60 days, as stated in Figure 1 , following the procedures already published ( Miotto et al, 2021a ; Miotto et al, 2021b ). A cuff was positioned around the tail of the animals and systolic blood pressure (SBP) was recorded by tail-cuff plethysmography system (PanLab LE5001, Barcelona, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 1 , on the 14th day of the treatment with DEX, all rats were anesthetized and the carotid artery was catheterized for direct BP measurements following the procedures previously described by our laboratory ( Herrera et al, 2016 ; Constantino et al, 2017 ; Herrera et al, 2017 ; Duchatsch et al, 2018 ; Jesus et al, 2020 ; Miotto et al, 2021a ; Miotto et al, 2021b ; Duchatsch et al, 2021 ; Tardelli et al, 2021 ). On the next day, BP was recorded in conscious freely moving rats using a Software LabChart Pro 7.1 (ADInstruments, NSW, Australia).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Guo et al 30 showed that female elderly rats that received perindopril treatment and performed PE had a higher capillary density increase in the soleus muscle compared to the group that performed only PE. Recently, Miotto et al 31 Studies investigating possible molecular mechanisms involving angiogenesis induced by PE and ACEi are still insufficient, some authors through animal experimentation, have shown ACEi (captopril) attenuated the increase in gene expression of VEGF receptor and protein production of VEGF 32,4 . Although there are no investigations about eNOS, PE and AECi, Silvestre et al 33 demonstrated that the treatment with perindopril did not inhibit angiogenesis submitted to ischemic surgery, this result was accompanied by an increase in eNOS.…”
Section: Physical Exercise and Aceimentioning
confidence: 99%